2015
DOI: 10.1007/s11910-015-0599-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Orthostatic Hypotension in Neurodegenerative Disease

Abstract: The autonomic nervous system appears to be uniquely susceptible to degeneration in disorders of α-synuclein pathology. Clinically, autonomic dysfunction in these disorders manifests as neurogenic orthostatic hypotension (nOH), a condition that results in substantial morbidity and mortality. nOH results from pathology affecting either the central autonomic pathways or peripheral autonomic nerve fibers. Determining the localization and pathophysiology of nOH is critical in effectively managing this disorder and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 94 publications
1
13
0
Order By: Relevance
“…Neurogenic OH can increase the risk of falls, particularly among older patients [ 8 , 9 ]. However, only limited information regarding the impact of nOH on quality of life among patients and caregivers has been published [ 10 12 ]. We designed a survey to gain a better understanding of the following areas: (1) scope of symptoms and burden of disease among patients with nOH, (2) effect of nOH symptoms on lives of patients from the perspective of caregivers, and (3) insights on the patient and caregiver journey from diagnosis to symptom management.…”
Section: Introductionmentioning
confidence: 99%
“…Neurogenic OH can increase the risk of falls, particularly among older patients [ 8 , 9 ]. However, only limited information regarding the impact of nOH on quality of life among patients and caregivers has been published [ 10 12 ]. We designed a survey to gain a better understanding of the following areas: (1) scope of symptoms and burden of disease among patients with nOH, (2) effect of nOH symptoms on lives of patients from the perspective of caregivers, and (3) insights on the patient and caregiver journey from diagnosis to symptom management.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with nOH are at risk for falls and serious injury due to BP dysregulation that may result in presyncope/syncope. 6,23 Earlier analyses suggested that droxidopa treatment of PD patients with nOH may reduce falls, and this deserves further investigation. 22 However, the patient burden of nOH may also extend beyond risk for falls and associated morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of the drop in BP and resultant insufficient perfusion of the brain, patients commonly experience the cardinal symptoms of nOH, including dizziness, lightheadedness, presyncope, or syncope . nOH increases the risk of falls and injuries from falls, and may cause patients to limit their daily activities because of fear of falling . It has been estimated that 30% to 58% of patients with PD have a BP decrease on standing that meets the consensus definition of nOH; approximately 20% of patients experience symptoms as a result of these hemodynamic changes …”
Section: Introductionmentioning
confidence: 99%
“…Falls increase the risk of injuries and increase healthcare resource use [62][63][64][65][66]. In patients with PD, symptoms of nOH are associated with increased risk of falls and impairment of activities of daily living [36, 67,68]. An increased rate of falls has been demonstrated even in patients with asymptomatic nOH when compared with patients with PD without nOH (odds ratio 6.726; P = 0.005) [27].…”
Section: Functional Psychosocial and Healthcare Resource Use Impactsmentioning
confidence: 99%